CAREER GUIDANCE SERVICES USING THE HOLLAND THEORY APPROACH TO STUDENT CAREER PLANNING - Anita Nurlaeli Riyadi (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
Middle school students, especially grade IX, are generally not able to make good career plans. They don't have much information about careers, whether it is about high school or educational specialties and jobs. Many students experience confusion regarding career planning to be made. One reason is due to the low level of student understanding of career planning, and a lack of understanding of one's own interests and talents, so that students feel that there is no purpose for planning a career. One of the guidance and counseling services is a career guidance service. The purpose of this study was to determine the effectiveness of John L. Holland's theoretical approach to career guidance services for class IX students of SMPN 5 Tasikmalaya. This study uses a quantitative descriptive approach in uncovering the effectiveness of career guidance services. The data collection technique used was purposive sampling. In this study, the sample used was 62 students divided into control and experimental groups. The results of this study indicate that the career guidance service with the theoretical approach of career planning for students of John L. Holland has proven to be effective.